IMPROVING WRITING AND READING SKILLS BY USING NEW METHODS AND ACTIVITIES - Abduvalieva Tursunoy (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article discusses effective methods of developing reading and writing skills when learning English as a second language. It is vital that language is the main factor of communication, and people try to learn the language in order to be good communicators. All languages, such as English, are also studied to achieve success in all spheres of society: education, medicine, economics or politics, and require a good command of all language skills. In particular, productive and receptive skills such as reading and writing play a crucial role in language learning and teaching. This document focuses on the importance of these skills and will explore effective, innovative and effective ways, methods and approaches. The ability to write described in this article is very important when teaching a foreign language; it helps students master the letters and sounds of the English language, its vocabulary and grammar, as well as develop habits and skills of pronunciation, speaking and reading.